ANALISIS PELAKSANAAN PROGRAM IMUNISASI DASAR LENGKAP (IDL) PADA BAYI DI PUSKESMAS KOTA SEMARANG (Studi Kasus pada Puskesmas Kedungmundu dan Puskesmas Candilama) - Isna Nurul Khomariah; Antono Suryoputro; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2018)
Immunization is one of the preventive basic health services that aims to reduce infant morbidity and mortality to avoid PD3I. Complete Basic Immunization Coverage in Semarang City has met the target, but PD3I cases are still found, namely in 2017 there were 2 cases of diphtheria, 143 cases of measles experienced an increase from 2016 and cases of hepatitis were as many as 102 cases and increased every year. The purpose of this study was to find out the description and analyze the implementation of the Complete Basic Immunization Program in infants at Kedungmundu Primary Health Care and Candilama Primary Health Care. This type of research is qualitative with a descriptive analytic approach. Data collection was carried out by in-depth interviews and based on purposive sampling criteria. Subjects in this study were 2 midwives of immunization holders as the main informants, 2 heads of PHC, 1 immunization program holder from DKK Semarang and 2 mothers of toddlers. The variables studied are man, money, material, method, planning, organization, implementation, assessment and environment.The results of this study are the differences in the analysis of the implementation of the Complete Basic Immunization Program between primary health care with low coverage and  primary health care with high coverage in the use of SOP, organizing parties that support immunization programs, implementation of immunization services in counseling, supervision of midwives compliance with SOP by quality and support teams family. In other indicators, the state of the PHC with low coverage is almost the same as the PHC with high coverage. All midwives in the two health care have not received special training on immunization, the funds needed for immunization come from the City Government, infrastructure facilities that are feasible in both PHC. Organizing is equally cross-sectoral, but the role of BPM in PHC with low coverage is still lack in reporting. The results of this study suggest that PHC to supervise using SOP checklists by involving the quality team, visiting BPM to obtain data, in collaboration with Gasurkes in delivering counseling.